Increased Dendrite Branching in AβPP/PS1 Mice and Elongation of Dendrite Arbors by Fasudil Administration - Couch, Brian A. (2010)
Amyloid-β (Aβ) overproduction and dendrite arbor atrophy are hallmarks of Alzheimer’s disease. The RhoA GTPase (Rho) signals through Rho kinase (ROCK) to control cytoskeletal dynamics and regulate neuron structure. Hyperactive Rho signaling destabilizes neurons leading to dendritic regression that can be rescued by genetic or pharmacological reduction of ROCK signaling. To understand what effect reduced ROCK signaling has on the dendrite arbors of mice that overproduce Aβ, we administered the ROCK inhibitor fasudil to AβPP/PS1 transgenic mice. We report that increased dendrite branching occurs in AβPP/PS1 mice and that fasudil promotes lengthening of the dendrite arbors of CA1 pyramidal neurons.